Antidepressant treatment and mortality risk in patients with dementia and depression: a nationwide population cohort study in Taiwan - Jian-An Su; Chih-Cheng Chang; Hsuan-Min Wang; Ko-Jung Chen; Yao-Hsu Yang; Chung-Ying Lin (SAGE Publishing, 2019)
Background: Dementia prevalence is increasing worldwide, and dementia is frequently comorbid with depression during its disease course. Additionally, safety concerns are rising regarding the prescription of psychotropic agents to patients with dementia. Thus, our study assessed the influence of prescribing antidepressants in dementia with depression on mortality risk, and the differences between classes of antidepressants. Methods: This study was a population-based retrospective cohort study that utilized the National Health Insurance (NHI) medical claims data on mental illness in Taiwan between 1998 and 2013. We identified 25,890 cases of newly diagnosed dementia with depression and divided them into two groups: antidepressant users and nonusers. All-cause mortality between the two groups and the effects of different antidepressants were analyzed. Results: Antidepressants reduced all-cause mortality in patients with dementia and depression after adjusting for all covariates. Furthermore, the effect was significant when antidepressant exposure was more than 168 cumulative defined daily dosages, and most classes of antidepressants had this protective effect. Conclusions: Antidepressant treatment showed significant protective effects in all-cause mortality for patients with dementia and depression. Most classes of antidepressants were effective, especially with longer treatment duration or higher dosage.